Depresión y su influencia en la interacción social de una mujer de 60 años de edad, del cantón Baba, Provincia de Los Ríos - Zurita Arteaga, Karla Janinna (2020)
The purpose of this case study is to determine the influence of depression on the social interaction of a 60-year-old woman, a resident of Canton Baba, Los Ríos province. To obtain the information, scientific research was applied, as well as basic psychological tools and techniques with the aim of reaching a presumptive diagnosis; and from it, propose a solution based on the application of cognitive behavioral psychotherapy. In addition, the information will serve as an instructive and guide for patients with depressive disorder, their relatives and experts in the field.